Selecting Proper Sand Control Method to Achieve Production Target Through Decision Making Approach (The Indonesian Journal of Business Administration, 2020)
PT.LKOC is one of the largest companies in Indonesia which is engaged in oil and gas. Considering the production sharing contract that will expire in August 2021, PT.LKOC chose the path for optimization in servicing of wells through workover and well service to maintain the level of oil production. In addition, PT.LKOC has another effort to maintain production by reducing the amount of lost production oil (LPO) which has a very high number. Writer use the why tree and Focus Group Discussion (FGD) to find the root cause of not achieving the production target. The less effective sand control method is a potential cause of this problem. Then after conducting focus group discussion, team have 3 alternatives and 4 criteria. In making alternative choices, the teams use the Analytic Hierarchy Process (AHP) as a structured method for analyzing alternatives. The sand control pump screen method is rated as the most effective method of suppressing very high LPO in Ridu field. In addition, the result of implementation the pump screen can reduce the LPO number from average 2,098 BOPD to 1,747 BOPD and improve the oil production 1,000 BOPD above from the estimation.Keywords: Sand control, LPO, decision making, AHP